Pediatric non-clinical drug testing principles, requirements, and practice - Hoberman, Alan M.; Lewis, Elise M. (Hoboken, N.J. : John Wiley & Sons, 2012)
"This book explains the importance and practice of pediatric drug testing for pharmaceutical and toxicology professionals. It describes the practical and ethical issues regarding non-clinical testing to meet US FDA Guidelines, differences resulting from the new European EMEA legislation, and how to develop appropriate information for submission to both agencies. It also provides practical study designs and approaches that can be used to meet international requirements. Covering the full scope of non-clinical testing, regulations, models, practice, and relation to clinical trials, this text offers a comprehensive and up-to-date resource"--Provided by publisher.
Machine generated contents note: Introduction and the history of pediatric nonclinical drug testing / Elise M. Lewis, Luc M. deSchepdrijver, Timothy P. Coogan -- Overview of pediatric diseases and clinical considerations on developing medicines for children / Bert Suys, Jose Ramet -- Nonclinical safety assessment for biopharmaceuticals : challenges and strategies for juvenile animal testing / Timothy P. Coogan -- FDA approach to pediatric testing / Robert E. Osterberg -- Pediatric drug development plans / Kimberly Brennan, Beatriz Silva Lima -- Application of principles of nonclinical pediatric drug testing to the hazard evaluation of environmental contaminants / Susan L. Makris -- Nonclinical testing procedures - pharmacokinetics / Loeckie L. de Zwart, Johan G. Monbaliu, and Pieter P. Annaert -- Preclinical development of a pharmaceutical product for children / Graham P. Bailey, Timothy P. Coogan, Luc M. De Schaepdrijver -- Juvenile toxicity study design for the rodent and rabbit / Alan M. Hoberman, and John Barnett Jr. -- Dog juvenile toxicity / Keith Robinson, Susan Y. Smith, and Andre Viau -- Use of the swine pediatric model / Paul C. Barrow -- Juvenile immuno-development in minipigs / Andre H Penninks ... [et al.] -- Use of primate pediatric model / Gerhard F. Weinbauer -- Approaches to rat juvenile toxicity studies and case studies : a pharmaceutical perspective / Susan B. Laffan, and Lorraine Posobiec.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Drug development -- United States; Pediatric pharmacology -- United States; Pediatrics -- United States -- Formulae, receipts, prescriptions -- Safety measures; Electronic books